الحركات الجسدية ودلالتها في الشعر العباسي - زيتونة مسعود, علي; مسعودي بنت خليفة , سمية; مسعودي ينت صالح (University of Eloued جامعة الوادي, 2024)
تناولت هذه الدراسة الحركات الجسدية ودلالاتها في الشعر العباسي و قد قامت على فكرة أساسية أهمها أن التواصل اللساني لا يقوم على حدود اللغة المنطوقة أو المكتوبة فحسب ،بل تعدى ذلك ليشمل حركات جسم الإنسان و سبب اختيارنا لهذا الموضوع هو قلة الدراسات و المباحث حولها و بيان أهميتها و دلالاتها، والتواصل بالحركات الجسدية ظاهرة قديمة الاستعمال منذ خلق الإنسان قد فطن لها أجدادنا القدماء و كانوا على وعي بدورها في التواصل و نجد الحديث عنها مبثوثا و متفرقا في ثنايا الكتب، و قد تحققت هذه الدراسة بالاستعانة بالمنهج الوصفي و التحليلي و التاريخي متكونة من مقدمة و فصلين و خاتمة معتمدين على مجموعة من المصادر و المراجع و قد استخلصنا مجموعة من النتائج أهمها: الدقة والمصداقية في توصيل الرسالة و توضيح معانيها و دلالتها بطريقة لا شعورية، وكذلك الإيجاز في اللفظ و التدفق بالمعاني و الدلالات، توضيح المعاني الخفية في ثنايا النص وقد ساعدت الشاعر في التعبير عن أغراض معينة مرتبة بالسياق الوارد فيه، والنص الشعري رسم الصورة الفنية و الذهنية ليجذب القارئ و يؤثر فيه، و تفجير عواطفه و مشاعره و الكشف عن مكنوناته المضمرة ، و نظرا لهذه المزايا فقد شكل التواصل بالحركات الجسدية عاملا مهما في التواصل البشري. This study addressed bodily movements and their significance in Abbasid poetry, based on the fundamental idea that linguistic communication is not limited to spoken or written language alone but extends to encompass the movements of the human body. The reason for choosing this topic is the scarcity of studies and research on it and to highlight its importance and significance. Non-verbal communication through bodily movements is an ancient phenomenon recognised by our ancestors, who were aware of its role in communication. References to it can be found scattered throughout the pages of books. This study was conducted using a descriptive, analytical, and historical approach, consisting of an introduction, two chapters, and a conclusion, drawing on a range of sources and references. The study yielded a number of key results, including accuracy and credibility in conveying the message and clarifying its meanings and significance in a non-arbitrary manner. Conciseness in expression and the flow of meanings and significance. larifying the hidden meanings within the text. The poet was aided in: Expressing specific purposes arranged within the context of the poetic text. Depicting artistic and mental imagery to attract and influence the reader. Triggering emotions and revealing underlying sentiments. Due to these attributes, non-verbal communication through bodily movements has become an important factor in human communication.
لسانيت عامة
Keywords: الحركات الجسدية، الشعر العباسي، الدلالات، الإشارة، التواصل، التأثير .; : Abbasid poetry; Body movements; communication; connotations; gestures; influence.